Connectionn Feeding Patterns with Picky Eater Behavior in Preschool Children Aged 4-5 Years - Susilawati Susilawati; Eni Subiastutik; Sugijati Sugijati; Vira Nabila (Minsight: Midwifery Insight and Innovation Journal, 2025)
Picky eating behavior is a common problem in preschool children that can affect nutritional intake and growth. Understanding the relationship between feeding patterns and picky eating behavior is important to help parents develop better feeding strategies. This quantitative study used a correlational analytical design with a cross-sectional approach. The study was conducted among 70 preschool children aged 4–5 years at KB-TK Al-Irsyad AlIslamiyyah, Sumbersari District, Jember Regency. A total of 60 children were selected using proportionate random sampling. Data were collected using the Child Eating Behavior Questionnaire (CEBQ) and a picky eater questionnaire. Statistical analysis was performed using the Chi-Square test. The findings showed that 45 children (75%) exhibited picky eater behavior, while 15 children (25%) did not. The Chi-Square test result showed a p-value of 0.030, indicating a significant relationship between feeding patterns and picky eater behavior. There is a significant relationship between feeding patterns and picky eater behavior in preschool children. Children with good feeding patterns are less likely to exhibit picky eating behavior. Therefore, parents should recognize their children’s eating patterns and provide a variety of foods to prevent picky eating tendencies.